2011
DOI: 10.3184/174751911x13099411630089
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Synthesis of 2-(4-Benzoyl-Piperazin-1-Ylmethyl)-5, 6-Dimethoxy-3-Methyl-[1, 4]Benzoquinone

Abstract: The title compound was prepared by a reaction sequence starting from 2, 3, 4, 5-tetramethoxytoluene via Blanc chloromethylation reaction, oxidation and alkylation. The described method provides a good yield of the heterocyclic-Coenzyme Q analogue and is suitable for the synthesis of other analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…9,10 Moreover, this is a relatively simple procedure, using easily accessible reagents and an easy separation, with good yields of products which are its main advantages. 11,12 Hence, we believe that this synthetic approach could be a useful addition to the reported methods for the preparation of flavone analogues. …”
Section: Resultsmentioning
confidence: 95%
“…9,10 Moreover, this is a relatively simple procedure, using easily accessible reagents and an easy separation, with good yields of products which are its main advantages. 11,12 Hence, we believe that this synthetic approach could be a useful addition to the reported methods for the preparation of flavone analogues. …”
Section: Resultsmentioning
confidence: 95%
“…The direct alkylation of piperazine produces a mixture of substitution products from which the isolation of mono-substituted compounds is difficult or impossible [6]. Hence, we developed a convenient and practical method for the synthesis of Nbenzylpiperazine 3, As shown in Scheme 1, firstly, commercially available anhydrous piperazine 1 reacted with two equivalents of piperazinium dihydrochloride 2 to form a monohydrochloride intermediate in situ.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolites of CoQ homologues, and a number of synthetic CoQ analogues ( Fig. 1) have been shown to be capable of inhibiting, activating, or occupying sites in the mitochondrial permeability transition pores [4][5][6][7][8][9][10]. Among the CoQ homologues, which have been synthesised previously, substituted benzoquinone derivatives bearing a heterocyclic substituent can be useful as blood platelet aggregation inhibitors, glycation inhibitors, vascular relaxants, and cardiovascular agents [9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…CoQ 10 is also sold as a drug or dietary supplement in many countries, and there is an increasing market demand. Many researches [3][4][5][6][7][8][9][10][11][12][13][14] have shown that some metabolites of CoQ 10 , and a number of synthetic CoQ analogues exhibit significant biological activities, such as inhibition of mitochondrial complex I, lipid peroxidation activity and blood platelet aggregation. Especially, some CoQ analogues with heterocyclic substituents could be developed as drugs, [12][13][14][15] so to find a simple and efficient synthetic route for its preparation is considerable incentive.…”
Section: Introductionmentioning
confidence: 99%